超声气管镜针吸活检在肺癌诊断及基因检测中的作用 (Zhongguo Fei Ai Za Zhi, 2018)
BACKGROUND AND OBJECTIVE: Endobronchial ultrasound guided transbronchial needle aspiration (EBUS-TBNA) has emerged as an innovative technique for diagnosis and staging of lung cancer. But whether the procedure can provide enough tissue for the detection of gene mutations is still to be defined. Here we evaluated the efficacy of lung cancer diagnosis and gene analysis using samples obtain via EBUS-TBNA. METHODS: Patients with suspected lung cancer and mediastinal lesions were referred for EBUS-TBNA. Diagnosis and sub-classifications were made by pathologists. Samples with non-squamous non small cell lung cancer sub type were tested for the EGFR and/or ALK mutations. RESULTS: A total of 377 patients were included in this study. The median needle passes were 2.07. Lung cancer was diagnosed in 213 patients. The diagnosis accuracy for malignancy was 92%. Epidermal growth factor receptor (EGFR) mutations, anaplasticlymphoma kinase (ALK) fusion genes and double genes analysis were successfully preformed in 84 (90%), 105 (95%) and 79 (90%) patients. The number of needle passes and the diameters of lymph node were not associated with the efficacy of gene testing in univariate analysis. However, samples of adenocarcinoma sub type showed a tendency associated with higher genotyping efficacy. CONCLUSION: Tissue samples obtained through EBUS-TBNA are sufficient for pathological diagnosis and genetic analysis of lung cancer. The pathology type of sample affected genotyping efficacy.